mycorrhizal contribution to plant productivity, plant nutrition and soil structure in experimental grassland - Heijden, Marcel G.A. van der; Streitwolf-Engel, Ruth; Riedl, Ralph; Siegrist, Sabine; Neudecker, Angelica; Ineichen, Kurt; Boller, Thomas; Wiemken, Andres; Sanders, Ian R (The New phytologist, 2006)
• Previous studies have shown that arbuscular mycorrhizal fungi (AMF) can influence plant diversity and ecosystem productivity. However, little is known about the effects of AMF and different AMF taxa on other important community properties such as nutrient acquisition, plant survival and soil structure. • We established experimental grassland microcosms and tested the impact of AMF and of different AMF taxa on a number of grassland characteristics. We also tested whether plant species benefited from the same or different AMF taxa in subsequent growing seasons. • AMF enhanced phosphorus acquisition, soil aggregation and survival of several plant species, but AMF did not increase total plant productivity. Moreover, AMF increased nitrogen acquisition by some plant species, but AMF had no effect on total N uptake by the plant community. Plant growth responses to AMF were temporally variable and some plant species obtained the highest biomass with different AMF in different years. Hence the results indicate that it may be beneficial for a plant to be colonized by different AMF taxa in different seasons. • This study shows that AMF play a key role in grassland by improving plant nutrition and soil structure, and by regulating the make-up of the plant community.